The Influence of Financial Performance on Audit Report Lag: Is it Strengthened by Company Size? - Andriani Dwi Oktaviani (Sekolah Tingg Ilmu Ekonomi Y.A.I Jakarta - Indonesia, 2025)
This study aims to examine the effect of profitability, liquidity, and solvency on audit report lag and the role of company size in strengthening this effect. The population of this study is non-primary consumer sector trading companies listed on the Indonesia Stock Exchange (IDX), totaling 142 companies. Based on the purposive sampling method, the companies used as samples were 81 companies with an observation period of 5 years, so that the number of observations was 405. The analysis technique used was the panel data regression analysis method processed using eviews 12 software. The results show that profitability does not have a negative effect on audit report lag, liquidity has a negative effect, and solvency has a positive effect on audit report lag. In addition, company size is not proven as a variable that strengthens the effect of liquidity and solvency on audit report lag. The novelty of this study is the company size variable as a moderating variable, the measurement uses a dummy, and the addition of the independent variable, namely liquidity. The implications of this study indicate that to reduce the occurrence of audit report lag, trading companies should pay attention to several factors that have an influence, especially liquidity and solvency. This debt level plays an important role in managing the audit duration and quality of financial reports, which will ultimately have a direct impact on the company's attractiveness to investors. Abstrak - Penelitian ini bertujuan untuk menguji pengaruh profitabilitas, likuiditas, solvabilitas terhadap audit report lag dan peran ukuran perusahaan dalam memperkuat pengaruh tersebut populasi dari penelitian ini yaitu perusahaan perdagangan sektor konsumen non-primer yang terdaftar pada Bursa Efek Indonesia (BEI) berjumlah 142 perusahaan. Berdasarkan metode purposive sampling, perusahaan yang dijadikan sampel berjumlah 81 perusahaan dengan periode pengamatan selama 5 tahun sehingga jumlah observasi ada 405. Teknik analisis yang digunakan adalah metode analisis regresi data panel yang diolah menggunakan software eviews 12. Hasil menunjukan bahwa profitabilitas tidak mempunyai pengaruh negatif terhadap audit report lag, likuiditas berpengaruh negatif, dan solvabilitas berpengaruh positip terhadap audit report lag. Selain itu, ukuran perusahaan tidak terbukti sebagai variabel memperkuat pengaruh likuiditas dan solvabilitas terhadap audit report lag. Keterbaruan dari penelitian ini adalah variabel ukuran perusahaan sebagai variabel moderating pengukurannya menggunakan dummy dan bertambahnya variabel independen yaitu likuiditas. Implikasi dari penelitian ini menunjukkan bahwa untuk mengurangi terjadinya audit report lag, perusahaan perdagangan sebaiknya memperhatikan beberapa faktor yang memiliki pengaruh, terutama likuiditas dan solvabilitas. Tingkat utang ini memiliki peranan penting dalam mengelola durasi audit dan kualitas laporan keuangan, yang pada akhirnya akan berdampak langsung pada daya tarik perusahaan bagi para investor.